A Case of Congenital Supernumerary Teeth in an Ovine Dental Pad. (December 2017) - Corbera, Juan Alberto; Morales, Immaculada; Martin, Sergio; Arencibia, Alberto; Gutierrez, Carlos
A rare case of congenital supernumerary teeth, also known as hyperdontia, observed in a healthy 8-month-old female ewe is presented. The congenital defect consisted of the presence of 2 incisor teeth embedded in the lateral areas of the dental pad. The anomaly was found during a routine physical examination and no other congenital abnormalities were found in the patient. No prior congenital abnormalities had been seen in the herd and the study of possible associated teratogenic factors was inconclusive. To the authors' knowledge, this ovine odontogenic abnormality has not been described in the literature and appears to be an extraordinarily rare condition.